PSA, TZI, RI OF PROSTATE AS RISK FACTORS OF URINARY RETENTION - Renaldo, Johan; Hardjowijoto, Sunaryo; Djojodimedjo, Tarmono; Budiono, Budiono (Indonesian Urological Association, 2013)
Objective: To evaluate some parameters as the predictors of urine retention incident in Benign Prostate Hyperplasia (BPH) patients. Materials & Methods: From May to August 2012, a total of 24 BPH patients aged 47-69 years with lower urinary tract symptomps (LUTS) including 12 patients with urine retention were participated in the study. Prostate specific antigen (PSA) examination was performed on all patients. For urine retention patients, PSA was performed 2 weeks after catheterization as the procedure may affect PSA levels. Transrectal ultrasonography (TRUS) was examined to assess total prostate volume (VTP), transitional zone volume (VZT), transitional zone index (IZT = VZT / VTP), and resistive index of prostate capsulary arteries. Statistic was utilized using simple and multiple logistic regression. Receiver operating characteristic (ROC) was calculated to assess the usefulness of parameters as a predictor of urine retention. Results: There was no significant difference in age between LUTS and BPH patients with urine retention (p = 0,487). There was no relationship between PSA and transitional zone index to incidence of urine retention in BPH patients (PSA; p = 0,173 and TZI; p = 0,192). Multiple logistic regression analysis showed only resistive index of prostate capsulary arteries which correlates with urine retention incidence (p = 0,014), with area under ROC 0,865 (95% CI 0,721 to 1,008) and cut-off value of > 0,675 as a predictor of urine retention incidence. Conclusion: Resistive index of prostate capsulary arteries by transrectal ultrasonography (TRUS) is a predictor of urine retention incidence in BPH patients.Key words: prostate specific antigen, transitional zone index, resistive index of prostate capsulary arteries, benign prostate hyperplasia, lower urinary tract symptoms, urine retention.